Pembiayaan Mudharabah, Musyarakah, Murabahah dan Tingkat Profitabilitas Bank Syariah Di Indonesia - Sri Indah Istiowati; Muslichah Muslichah (AFRE (Accounting and Financial Review), 2021)
The purpose of this study is to examine the effect of mudharabah, musharakah and murabahah financing on profitability. The population of this research is Islamic Banks in Indonesia that registered for five consecutive years (2015–2019). The sample of this research are 7 sharia banks, and 5 years periods resulted in 35 observation data. The multiple regression analysis model in used to test the hypothesis. The results of this study indicate that mudharabah, musharakah and murabahah financing have different influence on profitability. Musharakah and murabahah financing risk have negative influances on profitability. In contrast, mudharabah financing risk have positive influence on profitability of Sharia Banks in Indonesia.